Attention to women in situation of intrauterine fetal death: experiences of health professionals - Serafim, Taynnara Caroline; Camilo, Beatriz Helena Naddaf; Carizani, Mariana Rodrigues [UNESP]; Gervasio, Mariana De Gea; Carlos, Diene Monique; Salim, Natália Rejane (FapUNIFESP (SciELO), 2021)
OBJECTIVES: Understand the experiences of health professionals in obstetric care in relation to the situation of intrauterine fetal death. METHOD: Study of a qualitative approach, in which 11 health professionals participated. Data were collected through semi-open interviews and submitted to thematic content analysis. RESULTS: The professionals' difficulty in dealing with the topic and its invisibility during the training proved to be challenging. The lack of ambience and the forms of organization of attention reflected in the care for women and families who are undergoing intrauterine fetal death. The lack of strategies and spaces for sharing among professionals was directly related to the suffering and feeling of helplessness in the cases. FINAL CONSIDERATIONS: There is a need to develop strategies for changes in the model and organization of the service in the face of situations of fetal death, promoting spaces that are welcoming producers.